Book Review: "Sudden Wealth...It Happens." - Erika Rasure (Journal of Financial Therapy, 2013)
“Sudden Wealth…It Happens” is an exploration of circumstances that can drastically change one’s financial future. A collection of cautionary, yet inspiring tales, sets the tone for emphasizing the importance of sudden wealth financial management. What follows is a sudden wealth management toolkit intended to guide the recipient of a windfall down the path of financial success, and away from the path of financial ruin.
Keywords: financial therapy; financial planning; financial counseling